Temperature-dependent EXAFS Debye-Waller Factor of Structurally Distorted Crystalline Cadmium - TIEN, TONG SY (Physical Science: New Insights and Developments Vol. 1, 2025)
The extended X-ray absorption fine structure (EXAFS) technique is a widely employed probe of the dynamical behaviours and structural parameters in disordered systems. This is because EXAFS spectroscopy can contain information about local structures around X-ray absorbing atoms and gives interatomic distances and coordination numbers in crystal lattices. The temperature-dependent EXAFS Debye-Waller (DW) factor of the distorted crystalline cadmium (Cd) has been analysed using the cumulant expansion approach. The analysis procedure is based on evaluating the influence of temperature on the phase shift and amplitude reduction of EXAFS oscillation, which is expressed in terms of the EXAFS DW factor via the anharmonic EXAFS cumulants. The calculation model is developed based on the many-body perturbation approach using the correlated Debye model and anharmonic effective potential that depends on the structural characteristics of distorted crystalline cadmium. The anharmonic EXAFS cumulants are calculated in an explicit form by considering the phonon dispersion relations and the quantum and anharmonic effects. The numerical results of Cd agree well with those obtained using the experimental data and other models at various temperatures. The obtained results indicate that this theoretical model is useful for calculating and analysing the experimental EXAFS data of structurally distorted crystalline metals.